Sex Hormones and Healthy Psychological Aging in Women - Navarro-Pardo, Esperanza; Holland, Carol A.; Cano, Antonio (Frontiers in Aging Neuroscience, 2018)
Besides their key role in reproduction, estrogens have effects in several organs in the body, as confirmed by the identification of estrogen receptors (ER) in multiple tissues. There is experimental evidence that estrogens have significant impacts on the central nervous system (CNS), and a key question is to what extent the fall in estrogen levels in the blood that occurs with increasing age, particularly around and following the menopause, has an impact on the cognitive function and psychological health of women, particularly regarding mood. This review will consider direct effects of menopausal changes in estrogens on the brain, including cognitive function and mood. Secondary pathways whereby health factors affected by estrogen changes may interact with CNS functions, such as cardiovascular factors, will be reviewed as well insofar as they also have an impact on cognitive function. Finally, because estrogen decline may induce changes in the CNS, there is interest on clarifying whether hormone therapy may offer a beneficial balance and the impact of hormone therapy on cognition will also be considered.